Confronting the HIV/AIDS epidemic in the Caribbean : issues of migration (2004)
Looks at the spread of the HIV/AIDS in migrant populations. Examines factors contributing to prevalence of the disease in these populations. Focuses on issues that must be addressed in order to curb further spread of the disease.
Keywords: HIV